More and better video evidence for police investigations of shootings: Chicago's area technology centers. Issue 4 (5th July 2021) - Cook, Philip J.; Berglund, Anthony
Abstract : Purpose: The purpose of this study is to describe the creation, implementation, activities and rationale for the Area Technology Centers (ATCs), an innovation adopted by the Chicago Police Department's (CPD's) Bureau of Detectives (BoD) in 2019 for the purpose of supporting investigations of crimes of serious violence by deploying specialized teams of officers to gather and process video and digital evidence. Design/methodology/approach: This case study utilizes historical information and descriptive data generated by a record-keeping system adopted by the ATCs. Findings: The ATCs were developed as a collaboration between the CPD and the University of Chicago Crime Lab (a research center). The start-up was funded by a gift from the Griffin Foundation. Detectives have made extensive use of the services provided by the ATCs from the beginning, with the result that homicide and shooting investigations now have access to more video and digital evidence that has been processed by state-of-the-art equipment. The CPD has assumed budget responsibility for the ATCs, which is an indication of their success. The ATC teams have been assembled by voluntary transfers by sworn officers, together with an embedded analyst from the University of Chicago. Practical implications: The ATC model could be adopted by other large police departments. The study finds that ATCs can be effectively staffed by redeploying and training existing staff and that their operation does not require a budget increase. Social implications: By arguably making police investigations of shooting cases more efficient, the ATCs have the potential to increase the clearance rate and thereby prevent future gun violence. Originality/value: The ATCs are a novel response to the challenges of securing and making good use of video and digital evidence in police investigations.